The experience of daily life of acutely admitted frail elderly patients one week after discharge from the hospital - Andreasen, Jane (Int J Qual Stud Health Well-being, 2015)
INTRODUCTION: Frail elderly are at higher risk of negative outcomes such as disability, low quality of life, and hospital admissions. Furthermore, a peak in readmission of acutely admitted elderly patients is seen shortly after discharge. An investigation into the daily life experiences of the frail elderly shortly after discharge seems important to address these issues. The aim of this study was to explore how frail elderly patients experience daily life 1 week after discharge from an acute admission. METHODS: The qualitative methodological approach was interpretive description. Data were gathered using individual interviews. The participants were frail elderly patients over 65 years of age, who were interviewed at their home 1 week after discharge from an acute admission to a medical ward. RESULTS: Four main categories were identified: “The system,” “Keeping a social life,” “Being in everyday life,” and “Handling everyday life.” These categories affected the way the frail elderly experienced daily life and these elements resulted in a general feeling of well-being or non-well-being. The transition to home was experienced as unsafe and troublesome especially for the more frail participants, whereas the less frail experienced this less. CONCLUSION AND DISCUSSION: Several elements and stressors were affecting the well-being of the participants in daily life 1 week after discharge. In particular, contact with the health care system created frustrations and worries, but also physical disability, loneliness, and inactivity were issues of concern. These elements should be addressed by health professionals in relation to the transition phase. Future interventions should incorporate a multidimensional and bio-psycho-social perspective when acutely admitted frail elderly are discharged. Stakeholders should evaluate present practice to seek to improve care across health care sectors.